Smartphone Use and Psychological Well-Being Among College Students in China: A Qualitative Assessment - Dai, Cheng; Tai, Zixue; Ni, Shan (Frontiers in Psychology, 2021)
Background: Problematic smartphone use is widespread, and college-age youth faces an especially high risk of its associated consequences. While a promising body of research has emerged in recent years in this area, the domination of quantitative inquiries can be fruitfully and conceptually complemented by perspectives informed through qualitative research. Toward that end, this study aimed to interrogate the myriad behavioral, attitudinal, and psychological tendencies as a side effect of college students’ engagement with the smartphone in their everyday lived experience through in-depth interviews. Methods: We recruited 70 participants from seven college campuses hailing from different geographic regions in China, and conducted semi-structured in-depth virtual interviews via WeChat in November and December 2020. Subjective experiences, personal narratives and individual perceptions in the context of routine interaction with the smartphone were thematically analyzed through a reiterative process in an effort to detect prevailing threads and recurring subthemes. Results: The smartphone has established a pervasive presence in college students’ everyday life. Time-based use characteristics generated a typology of four distinct user groups: hypo-connected antagonists, balanced majority, hyper-connected enthusiasts, and indulgent zealots. Habitual usage falls on predictable patterns matched onto temporal, locale-based and contextual cues and triggers. Students’ dependency relationships with the smartphone have both functional and emotional dimensions, as prominently manifested in occasions of detachment from the device. Self-regulatory effort in monitoring and limiting use is significantly impacted by mental focus and personal goal setting. Perspectives from our qualitative data suggest the need for taking into account a variety of contextual cues and situational factors in dissecting psychological and emotional outcomes of smartphone use and abuse.